THE SURVEY OF SAFETY CULTURE IN RSUP Dr.KARIADI SEMARANG - Elyana Sri Sulistyowati; Septi Dewi Muninggar; Verarica Silalahi; Debi Ariyanto; Endang Fatmawati; Dharma Wahyu Edhy; Anggit Anandoyo (Jurnal Riset Kesehatan, 2019)
Patient safety in hospitals is a crucial issue as significant medication errors occur in some countries. Patient safety incidence is inevitably related to safety culture implemented in hospitals. This survey aims to investigate the dimension of patient safety serving as a strong area and dimension for potential improvement. This study used a cross-sectional approach involving 361 subjects in all units in RSUP Dr. Kariadi. Findings are presented in graphs and frequency tables. This study found three dimensions of strength area involving management support regarding patient safety (92.93%), organizational learning-continuous improvement (91.73%), and unit cooperation (86.1%). Meanwhile, the area for potential improvement involving employment (45.43%), incidence report frequency (58.07%), and open communication (60.67%). Dimensions serving as strength areas need to be maintained while dimension for potential improvement need for support to cultivate patient safety culture in RSUP Dr. Kariadi.